2014
DOI: 10.1162/jocn_a_00607
|View full text |Cite
|
Sign up to set email alerts
|

Disposed to Distraction: Genetic Variation in the Cholinergic System Influences Distractibility But Not Time-on-Task Effects

Abstract: Both the passage of time and external distraction make it difficult to keep attention on the task at hand. We tested the hypothesis that time-on-task and external distraction pose independent challenges to attention, and that the brain’s cholinergic system selectively modulates our ability to resist distraction. Participants with a polymorphism limiting cholinergic capacity (Ile89Val variant (rs1013940) of the choline transporter gene SLC5A7) and matched controls completed self-report measures of attention and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 53 publications
(73 reference statements)
11
84
0
Order By: Relevance
“…This SNP, when expressed in a human cell line, reduced choline uptake by about 40% (Okuda et al, 2002) that, given the rate-limiting nature of the CHT for ACh synthesis and release, would be expected to limit elevations of cholinergic neuromodulation. We found that I89V humans self-report greater vulnerability for distractors and dramatically exhibit such vulnerability when tested in a continuous attention task in the presence of content-rich distractors, and they fail to activate right frontal regions in the presence of a distractor (Berry, Blakely, Sarter, & Lustig, 2015; Berry et al, 2014). As is the case in rats that are STs, the cognitive performance of humans expressing the I89V CHT subcapacity variant is consistent with a bias away from top-down attentional control and toward bottom-up, cue-driven performance (Sarter, Lustig, Blakely, & Koshy Cherian, 2016).…”
Section: Sts and Gts As Models For Research On Opponent Cognitive-motmentioning
confidence: 81%
See 1 more Smart Citation
“…This SNP, when expressed in a human cell line, reduced choline uptake by about 40% (Okuda et al, 2002) that, given the rate-limiting nature of the CHT for ACh synthesis and release, would be expected to limit elevations of cholinergic neuromodulation. We found that I89V humans self-report greater vulnerability for distractors and dramatically exhibit such vulnerability when tested in a continuous attention task in the presence of content-rich distractors, and they fail to activate right frontal regions in the presence of a distractor (Berry, Blakely, Sarter, & Lustig, 2015; Berry et al, 2014). As is the case in rats that are STs, the cognitive performance of humans expressing the I89V CHT subcapacity variant is consistent with a bias away from top-down attentional control and toward bottom-up, cue-driven performance (Sarter, Lustig, Blakely, & Koshy Cherian, 2016).…”
Section: Sts and Gts As Models For Research On Opponent Cognitive-motmentioning
confidence: 81%
“…Poor attentional control is characterized by relatively unstable task performance, poor task compliance, and a limited capacity for restoring performance after exposure to distractors or other detrimental manipulations (Berry et al, 2014; Demeter & Woldorff, 2016; St. Peters, Demeter, Lustig, Bruno, & Sarter, 2011).…”
Section: Attention-associated Levels Of Cholinergic Neuromodulation Imentioning
confidence: 99%
“…However, concerns about reliability may be mitigated by the clear shift in the distributions seen when examining the individual subject data (i.e., effects are not driven by outliers; see especially Figure 3) and the consistency of findings across multiple analysis methods, including the use of an a priori BA 9 ROI drawn from an independent dataset. Furthermore, our primary hypothesis, Ile89Val hypoactivation of the right BA 9 response to attentional challenge, was grounded in findings bridging cognitive (Berry et al, 2014; Berry et al, in prep; Demeter et al, 2011; English et al, 2009; Kim et al, 2006), systems (Gill et al, 2000; Parikh et al, 2013; St Peters et al, 2011), and molecular (Okuda et al, 2002) neuroscience. Examining how the BA 9 response to attentional challenge was affected by cholinergic genetic variation was a logical next step in integrating these multidisciplinary findings, and there were strong a priori reasons to hypothesize the present results.…”
Section: Discussionmentioning
confidence: 97%
“…Participants contributed saliva samples for genotyping as previously described (Berry et al, 2014). In total, 67 Ile89Val heterozygotes were identified from this sample.…”
Section: Methodsmentioning
confidence: 99%
“…Also of potential relevance to these findings of individual differences in response to CDP-choline is the choline uptake transporter (CHT), which imports choline from extracellular space to presynaptic terminals for use in normal acetylcholine synthesis/cholinergic transmission (Sarter and Parikh 2005). As CHT capacity has been associated with variability in cognitive functioning (Sarter and Parikh 2009), and as human CHT gene polymorphisms have been associated with individual differences in cortico-limbic activation (Neumann et al 2006) and attentional processing (Berry et al 2014), genetic differences in CHT capacity may underly some of the inter-individual variability in acoustic change detection response to CDP-choline.…”
Section: Discussionmentioning
confidence: 99%